Effects of different bicarbonate on spirulina in CO2 absorption and microalgae conversion hybrid system - Zhang, Pengyu; Sun, Qian; Dong, Ye; Lian, Shaohan (Frontiers in Bioengineering and Biotechnology, 2023)
According to the characteristics of power plant flue gas emission and the requirements of reducing CO2 capture cost. CO2 absorption hybrid with microalgae conversion (CAMC) can avoid the challenges of heat consumption during absorbent desorption and nutrient consumption during microalgae culture. In this study, Na2CO3 and K2CO3 were selected as CO2 absorbers to generate NaHCO3 and KHCO3 as carbon sources for Spirulina platensis culture, and different concentrations of bicarbonate were set to explore the best carbon source. The results showed that Na2CO3 was a better absorbent for the CAMC system, which was beneficial for the growth of Spirulina, compared with K2CO3. When 0.3 mol/L NaHCO3 was added to the CAMC system, the highest biomass dry weight, carbon fixation rate and carbon utilization efficiency were obtained, which were 2.24 g/L, 230.36 mg/L/d and 26.71%, respectively. In addition, 0.3 mol/L NaHCO3 was conducive to protein synthesis, reaching 1625.68 mg/L. This study provided a feasible idea for power system to achieve carbon neutrality in the future.